Kinerja Ruas Jalan Poros Sultan Alauddin Kabupaten Gowa - Yeremia Risky Somba (Paulus Civil Engineering Journal, 2026)
Sultan Alauddin street is an access that connects Makassar City and the border of Gowa City. There are also densely populated areas, several shops, offices, and other public facilities. This road section is also an alternative section for drivers of two-wheeled and four-wheeled motorized vehicles and more than 4 wheels who choose to use this access instead of toll roads. It is often seen that heavy vehicles are heading (from the direction of Gowa to Makassar), while the direction of traffic on the section reviewed is from the direction (Makassar to Gowa), especially during the hours of going to work / school, logistics distribution by heavy vehicles, with the presence of heavy vehicles has the potential to reduce the capacity of the section. Based on the core of the problems obtained, this study aims to determine what the influence of heavy vehicles passing on traffic performance on the Sultan Alauddin Highway section. Data obtained from observations and surveys of traffic flow in the field will be analyzed with the combination in the book Indonesia Highway Capacity Manual 2014. The degree of saturation (DJ) is the ratio of road to capacity, which is used as a determination of the level of road performance. The highest saturation degree value on Jalan Sultan Alauddin occurred on Monday, with a value of 0.92.. Data analysis of the level of service on Jalan Sultan Alauddin from the results is known to be the level of not maximum use of road sections for vehicles that park or stop on the shoulder of the road so that it can interfere and hamper the performance of road sections.